NON PITTING TYPE PEDAL EDEMA WITH LITHIUM: A CASE REPORT - C., Parvathypriya; Philip, Jeslyn Mary; George, Christeena; R., Lakshmi (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: To report a case of lithium induced bilateral nonpitting pedal edema. Methods: The clinical data of a bipolar affective disorder patient with current episode of mania and psychotic symptoms who experienced bilateral non pitting pedal edema with lithium. Results: The patient was a 29 yr old female who developed bilateral non-pitting type pedal edema with lithium therapy with normal plasma lithium level (0.72mEq/l). She is a known case of bipolar affective disorder (BPAD) was admitted to psychiatry department with episode of mania with psychotic symptoms. She had history of drug induced hypersensitivity reaction with eosinophilia and systemic symptoms (DRESS) with oxcarbazepine and so the drug was discontinued and was started on tablet lithium 400 mg twice daily. On admission here, the dose of lithium was increased to 1200 mg/day. The patient gradually improved but she developed bilateral non-pitting pedal edema. Serum lithium concentration was normal and there were no other early symptoms of lithium toxicity. But as the patient's distress further increased with increasing pedal edema, it was decided to stop lithium altogether and to maintain the patient on tablet quetiapine 800 mg therapy for BPAD. Within one week of stopping lithium the edema on both her feet decreased significantly. Causality was assessed by naranjo causality assessment scale and a probable relationship was obtained between lithium and pedal edema with a score of 6. Conclusion: This case emphasises that regular physical examination and laboratory investigations are important for patients who are on lithium therapy. Clinicians should always be careful while initiating lithium treatment in a patient with respect to the initial dose and dose escalation even after a period of successful therapy with lithium, as minor dose escalation can cause major changes in the serum lithium concentration and thereby the patient's tolerability to lithium.